2010
DOI: 10.1038/nature09101
|View full text |Cite
|
Sign up to set email alerts
|

Nearby galaxies as pointers to a better theory of cosmic evolution

Abstract: The great advances in the network of cosmological tests show that the relativistic Big Bang theory is a good description of our expanding universe. But the properties of nearby galaxies that can be observed in greatest detail suggest a still better theory would more rapidly gather matter into galaxies and groups of galaxies. This happens in theoretical ideas now under discussion.In the standard cosmology [1] 4% of the mass of the universe is in the baryons of which stars and planets are made, 22% is nonbaryoni… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
193
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 177 publications
(195 citation statements)
references
References 67 publications
2
193
0
Order By: Relevance
“…The most massive halos, hosts for the brightest galaxies, are formed in regions with the highest local mass density. Less massive halos, hosts for the less bright galaxies, appear in regions with low local densities [94]. These situations appear to be the same as in our extragalactic neighborhood, but there are still problems.…”
Section: Why Scalar Field Dark Matter?mentioning
confidence: 82%
See 2 more Smart Citations
“…The most massive halos, hosts for the brightest galaxies, are formed in regions with the highest local mass density. Less massive halos, hosts for the less bright galaxies, appear in regions with low local densities [94]. These situations appear to be the same as in our extragalactic neighborhood, but there are still problems.…”
Section: Why Scalar Field Dark Matter?mentioning
confidence: 82%
“…These problems would be solved again if the structure grew faster than it does in the standard paradigm [94].…”
Section: Why Scalar Field Dark Matter?mentioning
confidence: 99%
See 1 more Smart Citation
“…Full sky galaxy surveys in the local Universe have revealed that about a third of the Local Volume contains only 3 galaxies (Peebles 2001;Peebles & Nusser 2010). As noted above, these surveys are about 80 per cent complete to mB = 17.5 (Karachentsev et al 2014).…”
Section: The Local Voidmentioning
confidence: 99%
“…Largely unaffected by the complexities and processes modifying galaxies in high-density environments, the isolated void regions must hold important clues to the formation and evolution of galaxies. This makes the relation between void galaxies and their surroundings an important aspect of the interest in environmental influences on galaxy formation [33,13,16,24,26].…”
Section: Introduction: Voids and Void Galaxiesmentioning
confidence: 99%